2016
DOI: 10.1007/s12078-016-9209-z
|View full text |Cite
|
Sign up to set email alerts
|

On the Colours of Odours

Abstract: Introduction In the present study, we explore the existence of cross-cultural differences in odour-colour correspondences between two European countries with geographic proximity and shared history: England and France. Moreover, we test whether a single chromatic arrangement can be used to represent an odour in both countries, even if the odour-colour association for this odour differed. Methods The responses of 59 British and 60 French participants to the same set of odorants were compared. In the second part… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
33
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(37 citation statements)
references
References 48 publications
3
33
1
Order By: Relevance
“…Results obtained in this study are closed to the ones reported in literature, where panelists have smelt odorants[30][31][32][33][34][35][36] (Supplementary…”
contrasting
confidence: 44%
See 3 more Smart Citations
“…Results obtained in this study are closed to the ones reported in literature, where panelists have smelt odorants[30][31][32][33][34][35][36] (Supplementary…”
contrasting
confidence: 44%
“…31,33 The 24 color patches (including white, black and grey) were printed in a white A4 size page and labelled with a capital letter and a number (Figure 1). 31,33 The 24 color patches (including white, black and grey) were printed in a white A4 size page and labelled with a capital letter and a number (Figure 1).…”
Section: Color Chartmentioning
confidence: 99%
See 2 more Smart Citations
“…There is also a growing awareness that cultural differences can influence the way in which people establish color-flavor associations (Shankar M.U. et al, 2010;Wan et al, 2014a,b;Jacquot et al, 2016;Wan et al, 2016).…”
Section: Introductionmentioning
confidence: 99%